Konsep Sosial Karakter dalam Buku Egrang Pinjaman dan Bangga - Imam Sugiarto; Tutuk Ningsih (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Childhood is a golden period to maximize personality formation. In the potential for social development of children's characters, the environment is very decisive in its formation, including what children read. The lack of social character possessed by children today presents its own challenges for parents. Researchers examine the story book Stilts Loans and Proud published by the Corruption Eradication Commission (KPK). This study is a qualitative descriptive study with the type of library research. This research results that the reading books published by the KPK contain integrity values, including; value of care and responsibility.